2008
DOI: 10.1177/0009922808323113
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hemorrhagic Edema of Infancy: Report of 4 Cases and Review of the Current Literature

Abstract: Acute hemorrhagic edema of infancy (AHEI) is a cutaneous leukocytoclastic vasculitis that usually occurs in children younger than 2 years of age. It is a rare disease characterized by mild fever, a violent onset of hemorrhagic skin lesions, and edema usually followed by a spontaneous and complete recovery. Although the etiology is unknown, AHEI often follows infections, drug treatment, or vaccination. In the present report, the authors describe 4 cases of AHEI and review the relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 10 publications
0
50
0
13
Order By: Relevance
“…Also, AlSufyani suggests the male to female ratio approximately 4.64/1 (AlSufyani, 2009). However, adding the reported cases between 2008 and 2010 (Alp et al, 2009;Babic et al, 2008;Cicero, 2008;Ferraira et al, 2010;Fiore et al, 2008;Halıcıoglu et al, 2010;Jain & Patel, 2008;Javidi et al, 2008;Kumar et al, 2008;Karremann et al, 2009;Obeid et al, 2008;Slutsky et al, 2010;Sites et al, 2008) makes the male to female ratio approximately 4.34/1. Also, Fiore and colleagues reported the ratios of boys as %67 and girls as %33 in their systematic review (Fiore et al, 2008).…”
Section: Sexmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, AlSufyani suggests the male to female ratio approximately 4.64/1 (AlSufyani, 2009). However, adding the reported cases between 2008 and 2010 (Alp et al, 2009;Babic et al, 2008;Cicero, 2008;Ferraira et al, 2010;Fiore et al, 2008;Halıcıoglu et al, 2010;Jain & Patel, 2008;Javidi et al, 2008;Kumar et al, 2008;Karremann et al, 2009;Obeid et al, 2008;Slutsky et al, 2010;Sites et al, 2008) makes the male to female ratio approximately 4.34/1. Also, Fiore and colleagues reported the ratios of boys as %67 and girls as %33 in their systematic review (Fiore et al, 2008).…”
Section: Sexmentioning
confidence: 99%
“…So, it can be suggested that AHEI can be diagnosed from newborn to 60 months of age. Actually, newly added reports of AHEI in English literature between 2008 and 2010 (Alp et al, 2009;Babic et al, 2008;Cicero, 2008;Ferraira et al, 2010;Fiore et al, 2008;Halıcıoglu et al, 2010;Jain & Patel, 2008;Javidi et al, 2008;Kumar et al, 2008;Karremann et al, 2009;Obeid et al, 2008;Slutsky et al, 2010;Sites et al, 2008) with the review by AlSufyani (AlSufyani, 2009) make the mean age approximately 16.56 months instead of 13.75 months reported by Alsufyani (Alsufyani, 2009). Indeed, there have been some reports of cases occurring beyond the age of 3 years; however, these cases have the features that overlap with those of Henoch-Schönlein purpura (Legrain et al, 1991;Shah et al, 2002).…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations